Enhanced recovery after surgery (ERAS) improves outcomes in elderly patients undergoing short-level lumbar fusion surgery: a retrospective study of 333 cases - Di Han; Peng Wang; Chao Kong; Xiaolong Chen; Shibao Lu (European Journal of Medical Research)
Abstract Background Degenerative lumbar disease significantly impairs the quality of life in elderly individuals, with short-segment lumbar degenerative disease being particularly prevalent. When conservative treatment proves ineffective, surgical intervention becomes the optimal choice for managing lumbar disease. The implementation of Enhanced Recovery After Surgery (ERAS) in spinal surgery has been progressively refined, leading to greater patient benefits. However, age and the associated decline in physiological function remain critical factors influencing surgical decision-making. Currently, there is a paucity of research focused on elderly patients undergoing lumbar fusion surgery to substantiate that advanced age does not diminish the benefits derived from ERAS in this demographic. Methods This is a retrospective cohort study of prospectively collected data. Patients who underwent short-segment (1 or 2 segments) transforaminal lumbar interbody fusion (TLIF) under the care of the same surgical team at our institution were recruited, and divided into no-ERAS-elder, ERAS-elder, and ERAS-younger groups. Subsequently, time to physiological function recovery and other outcomes were compared. Results The outcomes of the ERAS-elder group (n = 113) and the no-ERAS-elder group (n = 120) were compared. The overall physiological function recovery was significantly faster (6.71 ± 2.6 days vs. 8.6 ± 2.67 days, p = 0.01) in the ERAS-elder group. Next, the outcomes of the ERAS-elder group (n = 113) were compared with those of the ERAS-younger group (n = 100), and no significant difference in total physiological function recovery was found between the two groups (6.71 ± 2.6 days vs. 6.14 ± 1.63 days, p = 0.252). Conclusions This study shows that the implementation of the ERAS program can effectively shorten the recovery time of physiological function in elderly patients after short-segment lumbar surgery, reduce the incidence of some complications, alleviate pain, and significantly shorten the length of hospital stay. ERAS enables elderly patients to achieve outcomes comparable to those of younger patients.